PREVALENCE OF CAMEL TRYPANOSMIASIS AND ITS EFFECT ON PCV AS HEALTH INDICATOR - Ahmed Nour, Ibrahim; A. M,; Ismail,; A. A,; Majid,; A. A,; Sidig,; H. S,; Osman,; M. E,; Rahman,; A. H, (Journal of Veterinary Medicine and Animal Production, 2022)
Trypanosomosis (Guffar) is ranked as a major threat to camel industry. This paper reports the effects of trypanosomes on camel packed red cell volume (PCV) as depicted from field surveys to determine the prevalence of camel trypanosomosis in the Sudan. The PCV values of 894 examined camels were recorded. Thereafter, the range and the mean PCVs of infected and non-infected camels were determined. The effects of seasonal variation as well as the effects of trypanosomes in PCV values were also evaluated. The mean PCV value of parasitologically infected individuals was found to be significantly (p<0.01) lower than that of non-infected. Seasonal variations have no significant effect (p>0.05) on PCV. It was concluded that the degree of anaemia as estimated by PCV, can be used as indicator for camel trypanosomosis of herds in risk areas in the Sudan. This is may be helpful for strategic and effective use of trypanocides in trypanosomosis control. This may also reduce the distribution of drug resistant strains.